Eye movements during reading and their relationship to reading assessment outcomes in Swedish elementary school children - Andrea Strandberg; Gustaf Öqvist Seimyr; Mattias Nilsson; Per Östberg (Bern Open Publishing, 2022)
The characteristics of children's eye movements during reading change as they gradually become better readers. However, few eye tracking studies have investigated children's reading and reading development and little is known about the relationship between reading-related eye movement measures and reading assessment outcomes. We recorded and analyzed three basic eye movement measures in an ecologically valid eye-tracking set-up. The participants were Swedish children (n = 2876) who were recorded in their normal school environment. The relationship between eye movements and reading assessment outcomes was analyzed in using linear mixed effects models. We found similar age-related changes in eye movement characteristics as established in previous studies, and that eye movements seem to correlate with reading outcome measures. Additionally, our results show that eye movements predict the results on several tests from a word reading assess- ment. Hence eye tracking may potentially be a useful tool in assessing reading development.